INDEK BIOTIK FAMILI SEBAGAI INDIKATOR KUALITAS AIR SUNGAI GAJAHWONG YOGYAKARTA - Djumanto Djumanto; Namastra Probosunu; Rudy Ifriansyah (Universitas Gadjah Mada, 2013)
The purpose of this research was to determine water quality level of Gajahwong River, Yogyakarta with the present of macroinvertebrate as biologycal indicators. The sampling was conducted in the Gajahwong River ﬂ ow from Pakem subdistrict in Sleman regency to Pleret subdistrict in Bantul regency. There were six sampling stations, and sampling was conducted once a week for two months from mid October to December 2011. Samples of macroinvertebrate were collected by poking substrate in front of surber net mouth so that macroinverterbrate were drifted into surber and trapped in pocket net. Samples were preserved in 5% formaldehide solution then identiﬁ catiﬁ ed and anlyzed in the laboratory.The species number of macroinvertebrate were analyzed as biotic index, such as diversity index, evenness index, dominance index and biotic family index (BFI). Environment parameter measured include physical and chemical properties. The physical parameter collectednamely subtrate type, river depth and stream width, ﬂ ow velocity, temperature and total suspended solid (TSS). The chemical parameter collected namely dissolved oxygen, free CO2, alcalinity,organic matter and pH. The results showed that ﬂ ow rate was varied 0.51-0.80 m/det decrease to downstream direction.The water depth was ranging from 19.9 to 49.8 cm tend to increase downstream direction. Total suspended solid (TSS) was ranging from 8.5 to 14.2 mg/l and tend to be higher in the central city of Yogyakarta. Dissolved oxygen concentration was 6.0-7.2 mg/l while CO2 was 0.7-1.9 mg/l. Organic matter was 22.8-25.1 mg/l and pH was in the range of neutral. The density of macroinvertebrate was 88 individual/m2, the taxa number in each station was 7-12 species, diversity index was 1.48-2.09, evenness index 0.76-0.85 and dominance index was 0.10-0.27, and there was not found dominance organism among the stations samplings. The highest density was Limnaea tranculata and Potamopyrgus jenkinsi. Index biotic family ranging from 5.95 to 6.64 showing the water environment was poor and there has been pollution caused by garbage disposal of communities surround the river also waste disposal from resident along the watershed.